2007
DOI: 10.1152/ajpcell.00401.2006
|View full text |Cite
|
Sign up to set email alerts
|

Class A scavenger receptor-mediated cell adhesion requires the sequential activation of Lyn and PI3-kinase

Abstract: Class A scavenger receptors (SR-A) participate in multiple macrophage functions including macrophage adhesion to modified proteins. SR-A-mediated adhesion may therefore contribute to chronic inflammation by promoting macrophage accumulation at sites of protein modification. The mechanisms that couple SR-A binding to modified proteins with increased cell adhesion have not been defined. In this study, SR-A expressing HEK cells and SR-A+/+ or SR-A−/− macrophages were used to delineate the signaling pathways requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 32 publications
4
46
0
Order By: Relevance
“…by guest www.bloodjournal.org From insensitive to Src inhibition by PP2. 53 Although the prophagocytic receptors involved may differ, the signal transduction events found to be important for uptake of Ox-RBCs by RPM in the present study are in agreement with that described for uptake of apoptotic T cells by the same macrophage population. 54 In conclusion, our findings extend the previous knowledge on CD47 and its function to inhibit phagocytosis of RBCs, to also include experimentally senescent RBCs.…”
Section: Role Of Cd47 In Phagocytosis Of Senescent Rbcs 4265supporting
confidence: 91%
“…by guest www.bloodjournal.org From insensitive to Src inhibition by PP2. 53 Although the prophagocytic receptors involved may differ, the signal transduction events found to be important for uptake of Ox-RBCs by RPM in the present study are in agreement with that described for uptake of apoptotic T cells by the same macrophage population. 54 In conclusion, our findings extend the previous knowledge on CD47 and its function to inhibit phagocytosis of RBCs, to also include experimentally senescent RBCs.…”
Section: Role Of Cd47 In Phagocytosis Of Senescent Rbcs 4265supporting
confidence: 91%
“…Post et al showed that class A scavenger receptor–mediated cell adhesion activates pertussistoxin–sensitive Gi/o proteins and formation of focal adhesion complexes by mouse peritoneal macrophages. 136 Nikolic et al 137 confirmed the results of Post et al 136 showing that SR-A–dependent adhesion was via activation of Gi/o protein. Nikolic et al further showed that SR-A–mediated cell spreading required the sequential activation of the Src tyrosine kinase Lyn and PI3K.…”
Section: Intracellular Signalingsupporting
confidence: 53%
“…These results are, to our knowledge, the first demonstration of an interaction (direct or indirect) between SR-A and a RTK. A variety of previous studies [75,76,84,85] has provided indirect evidence that SR-A associates with tyrosine kinases, based in most cases on inhibitor studies and use of (A) Coimmunoprecipitation of PMø following AC exposure. PMø from 129P3/J mice (upper gel) or SR-AϪ/Ϫ mice (lower gel) were exposed to fivefold excess of AC for various times as indicated.…”
Section: Discussionmentioning
confidence: 99%